2013
DOI: 10.1128/jvi.03046-12
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus L-E1A Activates Transcription through Mediator Complex-Dependent Recruitment of the Super Elongation Complex

Abstract: The adenovirus large E1A (L-E1A) protein is a prototypical transcriptional activator, and it functions through the action of a conserved transcriptional activation domain, CR3. CR3 interacts with a mediator subunit, MED23, that has been linked to the transcriptional activity of CR3. Our unbiased proteomic analysis revealed that human adenovirus 5 (HAdv5) L-E1A was associated with many mediator subunits. In MED23-depleted cells and in Med23 knockout (KO) cells, L-E1A was deficient in association with other medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…A number of previous immunoprecipitation studies using the well-defined hAd5 E1A mutant dl1102 (18) have identified the interaction of TRRAP (8, 10) and p400 (11) with the E1A domain encompassing residues 26 to 35. During our unbiased proteomic analyses of cellular proteins associated with L-E1A and S-E1A (20,22), we detected associations of several proteins (in addition to TRRAP, p400, and GCN5) that we reasoned might be constituents of the TRRAP/p400 and TRRAP-GCN5 complexes. These proteins included Tip49, Tip50, BAF53, c-MYC, MYCBP, and ENY2.…”
Section: Defining the Transforming Activity Of E1a N-terminal Domainsmentioning
confidence: 93%
See 1 more Smart Citation
“…A number of previous immunoprecipitation studies using the well-defined hAd5 E1A mutant dl1102 (18) have identified the interaction of TRRAP (8, 10) and p400 (11) with the E1A domain encompassing residues 26 to 35. During our unbiased proteomic analyses of cellular proteins associated with L-E1A and S-E1A (20,22), we detected associations of several proteins (in addition to TRRAP, p400, and GCN5) that we reasoned might be constituents of the TRRAP/p400 and TRRAP-GCN5 complexes. These proteins included Tip49, Tip50, BAF53, c-MYC, MYCBP, and ENY2.…”
Section: Defining the Transforming Activity Of E1a N-terminal Domainsmentioning
confidence: 93%
“…The cell lysates were passed through a 26-gauge needle attached to a 1-ml syringe 10 times and treated with DNase for immunoprecipitation of TRRAP and p400. The lysates were precleared using protein A-agarose fast flow (P3476 Sigma) and immunoprecipitated with the antibodies indicated in the figures, as described previously (22). The bound proteins were resolved by NuPAGE Novex (Life Technologies) 3 to 8% Tris-acetate gels with Tris-acetate running buffer (for TRRAP and p400), 10% Bis-Tris gels with MOPS (morpholinepropanesulfonic acid) running buffer (for c-MYC), or 4 to 12% Bis-Tris gel with MES (morpholineethanesulfonic acid) running buffer (for all other proteins) and analyzed by Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…HPV16 E7, like E1A, can also bind to another component of TFIID, TAF110 (Mazzarelli, Atkins et al 1995), although the consequences of this interaction are not known. E1A can also interact directly with the Mediator complex and with the transcriptional elongation machinery, recruiting them to promoters to drive transcription (Vijayalingam and Chinnadurai 2013). Whether E7 has a similar activity is not known.…”
Section: Transcription Factors Regulated By E7mentioning
confidence: 99%
“…The CDK9-related pathway regulates a wide range of functions in mammalian cell biology [112, 24] and the replication program of numerous viral agents, such as the human immunodeficiency virus type 1 (HIV-1) and HIV-2 [25, 56], Epstein-Barr virus (EBV) [57], human T-lymphotropic virus type 1 (HTLV-1) [58, 59], human cytomegalovirus (hCMV) [60, 61], herpes simplex virus 1 (HSV-1) [62, 63], human adenovirus [64], and influenza A virus [65] (Table 2). Moreover, dysfunctions in the CDK9-related pathway are related with several forms of human tumors [9, 13, 2628, 6668] and cardiac hypertrophy [6975].…”
Section: Introductionmentioning
confidence: 99%